Arterial Disease Ulcers, Part 2: Treatment. Issue 1 (January 2015) - Weir, Gregory Ralph; Smart, Hiske; van Marle, Jacobus; Cronje, Frans Johannes; Sibbald, R. Gary
Abstract : PURPOSE: The purpose of this learning activity is to provide information about therapeutic clinical intervention options based on the pathophysiology of arterial ulcers. TARGET AUDIENCE: This continuing education activity is intended for physicians and nurses with an interest in skin and wound care. OBJECTIVES: After participating in this educational activity, the participant should be better able to: Identify assessments needed to guide treatment choices for arterial ulcers. Select treatment options for arterial ulcers under varying clinical circumstances. ABSTRACT: Objectives: The objectives of this article are to describe the therapeutic options available and develop an appropriate clinical approach suitable to the individual needs of the patient with arterial insufficiency, based on the wound bed preparation paradigm. 1 This information will also assist in the integration of decision making regarding appropriate clinical intervention in an interprofessional team approach, according to the International Inter-professional Wound Caring Model 2012, 2 with inclusion of patient-centered concerns within the patient's circle of care.